2013
DOI: 10.1186/2193-1801-2-129
|View full text |Cite
|
Sign up to set email alerts
|

Gamma radiation mediated green synthesis of gold nanoparticles using fermented soybean-garlic aqueous extract and their antimicrobial activity

Abstract: Aspergillus oryzae was used to enhance the mobilization of antioxidants of soybean matrix along with garlic as a co-substrate by modulating polyphenolic substances during solid-state fermentation. Mobilized polyphenols were used as a green tool for synthesis and stabilization of gold nanoparticles (AuNPs). The radiation-induced AuNPs synthesis is a simple, clean and inexpensive process which involves radiolysis of aqueous solution that provides an efficient method to reduce metal ions. Gamma irradiated aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 32 publications
(35 reference statements)
1
16
0
Order By: Relevance
“…These results revealed that AuNPs synthesized from gum kondagogu demonstrated effective antibacterial activity in Gramnegative than in Gram-positive bacteria. The present results agree well with the work of other researchers [42]. It can be suggested that Gram-negative strains of bacteria (E. coli) with thin cell wall is more susceptible to cell wall damage compared to Gram-positive strain bacteria (B. subtilis) with a thick cell wall.…”
Section: Antibacterial Activitysupporting
confidence: 93%
“…These results revealed that AuNPs synthesized from gum kondagogu demonstrated effective antibacterial activity in Gramnegative than in Gram-positive bacteria. The present results agree well with the work of other researchers [42]. It can be suggested that Gram-negative strains of bacteria (E. coli) with thin cell wall is more susceptible to cell wall damage compared to Gram-positive strain bacteria (B. subtilis) with a thick cell wall.…”
Section: Antibacterial Activitysupporting
confidence: 93%
“…13 Figure 3(a) shows. Clove (Syzygium aromaticum) extract is after reaction with gold ions, this absorption band shows shift towards higher wave number with the loss in intensity [16] [17]. This observation indicates that eugenol molecules may be involved in the reduction of the surface of gold ion.…”
Section: Chemical Functional Group Determinate By Ftirmentioning
confidence: 83%
“…Although the rising attention being synthesis of AuNPs from natural plant extract, because the bio-reduction mechanism remains to have been elucidate. El-Batal et al [39] demonstrated that AuNPs synthesized from Antigonon leptopus leaf extract containing metabolites and biomolecules observed through FTIR analysis were responsible for the bioreduction of Au ions as well as in soybean-garlic aqueous extract have been reported. The different functional groups with their corresponding stretches obtained in the presently synthesized AuNPs are in agreement with the previous reported of Varshney et al [40].…”
Section: Discussionmentioning
confidence: 99%